Analisis Pengaruh Bukaan terhadap Sirkulasi Udara dan Pencahayaan Alami pada Ruang Kamar Bangunan Asrama Mahasiswa Kepulauan Riau: Studi Kasus : Asrama Mahasiswa Putra Kepulauan Riau, Umbulharjo, Yogyakarta - Muhammad Farhan; Supriyanta Supriyanta (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Air circulation and natural lighting are among the key aspects influencing the comfort of room usage, particularly in dormitory buildings inhabited by university students. This study aims to explore thermal comfort more deeply, focusing on air circulation and natural lighting within student dormitory rooms in the Riau Islands. A qualitative method was employed, collecting up-to-date data on the selected building. Building simulations using Computational Fluid Dynamics (CFD) and DIALux were conducted to analyze the speed of air circulation and the quality of natural lighting within the rooms. The results reveal that prior to evaluation, the dormitory rooms faced thermal issues related to poor air circulation and insufficient natural lighting. Wind speed was recorded at less than 2 m/s, and the incoming and outgoing airflow collided due to the presence of only one ventilation access. The evaluation using cross-ventilation through room openings showed a positive impact on indoor air circulation, increasing wind speeds to 2–4 m/s. The cross-ventilation concept also enhanced the discharge and exchange of indoor air, preventing air stagnation. In terms of natural lighting, the simulation showed that lighting intensity in several rooms was below the minimum standard of 250 lux, particularly in areas far from the window openings. After modifications to the window layout and the addition of secondary light-transmitting elements, the lighting level significantly improved to meet the recommended standard. These findings highlight the importance of incorporating both passive ventilation and natural lighting strategies in student dormitory designs. Improving these environmental aspects not only enhances thermal comfort but also supports the health, productivity, and well-being of the residents. This study contributes to the growing body of research on sustainable dormitory design and can be used as a reference for future architectural planning and policy improvements.